Beginning Ubuntu Linux - Thomas, Keir.; Channelle, Andy.; Sicam, Jaime (New York, NY : Apress, 2009)
A guide to Ubuntu Linux covers such topics as installation, hardware components, the BASH shell, multimedia, office tasks, software instllation and removal, and data backup.
"The complete guide to Ubuntu--includes everything you need to take advantage of the world's favorite Linux opertating system."--Cover.
Includes index.
Keywords: Linux; Operating systems (Computers)